ASSISTANCE IN MSME DEVELOPMENT THROUGH MARKETING OPTIMIZATION AND PRODUCT INNOVATION IN BULU VILLAGE - Endah Emiarti (Tarqabin Nusantara Group, 2025)
Introduction :The Community Service Team seeks to improve the quality of Bulu Village MSME products by carrying out activities that have never previously been carried out by the Bulu Village community related to product development. Next, the team provides innovation to existing products but has not developed over time. Objective: This research aims to develop MSME products through Digital Marketing Optimization. Method: MSME players play an important role in developing their products. As an approach to this event, the team conducted a survey of obstacles to the development of the MSME product, and collaborated with related parties to expedite the activities being held. Results: some MSMEs have very little knowledge regarding digital marketing, the importance of halal certification labels, and attractive product packaging.